THE IMPACT OF CRUDE OIL PRICE AND THE GLOBAL MARKET ON THE NIGERIAN EXCHANGE RATE - Okonkwo , Chidi Ukwuoma; Chukwuma, Ugo Donald; Ujumadu , Rosary Ngozi; Godwin , Emmanuel Tochukwu (ESUT JOURNAL OF SOCIAL SCIENCES, 2024)
This paper investigates the impact of crude oil prices and global market volatility on the USD-NGN exchange rate using a Vector Error Correction Model (VECM). The data utilized for this work was daily data on crude oil prices, S&P 500 index, and the USD-NGN exchange rate from 3rd June 2020 to 31st May 2024. The study finds that there is a significant long-run relationship between the variables, with crude oil prices having a negative impact on the exchange rate and global market volatility having a positive impact. The results suggest that the exchange rate is highly sensitive to changes in crude oil prices and global market volatility, and that these factors have a significant impact on the exchange rate in both the short and long term. It was however noted that S&P 500 does not have a direct impact on the exchange rate in the short run. The study’s findings have important implications for policymakers in Nigeria, who must navigate the challenges of managing the exchange rate in a highly volatile global economy.